Engaging Future Healthcare Professionals as Caregivers to Hospice Patients in Comfort Care Homes. (June 2023) - Melekis, Kelly; Weisse, Carol S.; Phillips, Emma
Most people wish to die at home yet significant barriers exist in accessing care in one's home, especially for individuals with caregiver and/or housing instability. Across the U.S., residential homes for the dying are opening to address gaps in end-of-life care by recruiting community members to serve as caregivers to hospice patients during their final days. This paper describes a blended-experiential training program, informed by both an evidence-based educational framework and transformative learning theory, that trains undergraduate students to serve as surrogate family members to hospice patients in residential care homes. This study analyzed data from a sample of undergraduate students (n = 35) who participated in an 8-week program. Applying Kirkpatrick's evaluation model, study results indicate the program provided essential knowledge and skills in end-of-life care, benefiting both student learning outcomes and resident care.